Maluku Economic Recovery During the Covid-19 Pandemic and Entering the New Normal Era - Maryam Sangadji; Fahrudin Ramly; Yuyun Yuniarti Layn (MediaTrend, 2021)
Covid-19 globally has affected all sectors, and the lock down has aggravated world economic conditions, including Maluku Province. The research objectives are (1) to describe the sectors affected by the Covid-19 pandemic in terms of economic growth; (2) Describe the impact of covid-19 on the workforce; (3) Knowing the policies carried out by local governments in handling the socio-economic impacts of Covid-19; (4) Formulating a strategy for economic recovery from the impact of covid-19 and entering the new normal era. The method used in this research is descriptive quantitative, from the data published by competent government agencies. The results showed (1) out of 17 sectors, there were 13 sectors that experienced a contraction in economic growth, showing that the initial impact of Covid-19 in Jakarta had contributed to the economic contraction in Maluku in tw 1 and tw-2, economic growth declined due to PSBB in the city. Ambon. (2) the number of unemployed increases with the number of layoffs and workers who are laid off. (3) Regional government policies are very maximal in terminating the chain of transmission but have not been able to reduce the level of spread, the longer efforts to deal with the transmission chain through PSBB will have an increasingly impact on the economy and (4) Economic recovery strategies can be implemented through five activities in 2020 in the third quarter to to IV and in the year 2021